Description of Warileya lumbrerasi n. sp. (Diptera: Psychodidae) from Peru - Elena Ogusuku; J Enrique Perez; Clive R Davies; Pablo Villaseca (Memorias do Instituto Oswaldo Cruz, 1996)
Warileya lumbrerasi n. sp. is described from the northern Peruvian Andes. This species was collected inside houses, and is the seventh species described within the genus Warileya Hertig, 1948.